High-throughput single nanoparticle detection using a feed-through channel-integrated nanopore. Issue 43 (24th October 2019) - Tsutsui, Makusu; Yamazaki, Tomoko; Tatematsu, Kenji; Yokota, Kazumichi; Esaki, Yuko; Kubo, Yukari; Deguchi, Hiroko; Arima, Akihide; Kuroda, Shun'ichi; Kawai, Tomoji
Abstract : Feeding viral solution to a solid-state nanopore through a controlled fluid-flow enables high-throughput single-virus detection. Abstract : The outstanding sensitivity of solid-state nanopore sensors comes at a price of low detection efficiency due to the lack of active means to transfer objects into the nanoscale sensing zone. Here we report on a key technology for high-throughput single-nanoparticle detection which exploits mutual effects of microfluidics control and multipore electrophoresis in nanopore-in-channel units integrated on a thin Si3 N4 membrane. Using this novel nanostructure, we demonstrated a proof-of-concept for influenza viruses via hydropressure regulation of mass transport in the fluidic channel for continuous feeding of biosamples into the effective electric field extending out from the nanopores, wherein the feed-through mechanism allowed us to selectively detect charged objects in physiological media such as human saliva. With the versatility of nanopore sensing technologies applicable to analytes of virtually any size from cells to polynucleotides, the present integration strategy may open new avenues for practical ultrasensitive bioanalytical tools.